A Review on the Role of Metabolomics in Kidney Disease: Current Applications and Future Perspectives - Aghaei, Pardis; Nassiri, Nadereh; Akbari, Kasra; Aghaei, Goharnaz; Moghtaderi, Mastaneh (Journal of Pediatric Nephrology, 2025)
transplantation complications, and nephrolithiasis, pose significant global health challenges. Current diagnostic tools often detect the disease at advanced stages, limiting opportunities for early intervention. This narrative review evaluated the role of metabolomics in enhancing the understanding, diagnosis, and management of major kidney disorders, drawing exclusively on recent peer-reviewed studies. The review synthesized findings from comprehensive urine and plasma metabolomic analyses using nuclear magnetic resonance (NMR) and mass spectrometry (MS) platforms in pediatric and adult patients across multiple kidney settings. Metabolomics reveals disease-specific metabolic signatures, enabling the early detection of renal injury, differentiation between disease subtypes, and prediction of outcomes. In CKD, altered profiles of amino acids, energy metabolites, and gut-derived compounds correlate with disease progression. In AKI, early fluctuations in citrate, branched-chain amino acids, and bile acids demonstrate diagnostic and prognostic potential. In kidney transplantation, metabolomics aids in the detection of acute rejection and drug-induced toxicity. For nephrolithiasis, changes in oxalate and citrate metabolism reveal insights into gut-kidney axis interactions. The integration of metabolomics with other omics (genomics, proteomics, and microbiomics) enhances mechanistic understanding and supports the development of precision nephrology. Metabolomics is redefining kidney disease evaluation by providing sensitive, real-time, and non-invasive insights into renal pathophysiology. Continued advances in analytics, data integration, and clinical validation will be essential for translating these findings into personalized nephrology practice.